Structure of the 1,N(2)-Etheno-2′-deoxyguanosine Lesion in the 3′-G(εdG)T-5′ Sequence Opposite a One-Base Deletion - Shanmugam, Ganesh (American Chemical Society, 2010)
[Image: see text] The structure of the 1,N(2)-ethenodeoxyguanosine lesion (1,N(2)-εdG) has been characterized in 5′-d(CGCATXGAATCC)-3′·5′-d(GGATTCATGCG)-3′ (X = 1,N(2)-εdG), in which there is no dC opposite the lesion. This duplex (named the 1-BD duplex) models the product of translesion bypass of 1,N(2)-εdG by Sulfolobus solfataricus P2 DNA polymerase IV (Dpo4) [Zang, H., Goodenough, A. K., Choi, J. Y., Irimia, A., Loukachevitch, L. V., Kozekov, I. D., Angel, K. C., Rizzo, C. J., Egli, M., and Guengerich, F. P. (2005) J. Biol. Chem. 280, 29750−29764], leading to a one-base deletion. The T(m) of this duplex is 6 °C higher than that of the duplex in which dC is present opposite the 1,N(2)-εdG lesion and 8 °C higher than that of the unmodified 1-BD duplex. Analysis of NOEs between the 1,N(2)-εdG imidazole and deoxyribose H1′ protons and between the 1,N(2)-εdG etheno H6 and H7 protons and DNA protons establishes that 1,N(2)-εdG adopts the anti conformation about the glycosyl bond and that the etheno moiety is accommodated within the helix. The resonances of the 1,N(2)-εdG H6 and H7 etheno protons shift upfield relative to the monomer 1,N(2)-εdG, attributed to ring current shielding, consistent with their intrahelical location. NMR data reveal that Watson−Crick base pairing is maintained at both the 5′ and 3′ neighbor base pairs. The structure of the 1-BD duplex has been refined using molecular dynamics calculations restrained by NMR-derived distance and dihedral angle restraints. The increased stability of the 1,N(2)-εdG lesion in the absence of the complementary dC correlates with the one-base deletion extension product observed during the bypass of the 1,N(2)-εdG lesion by the Dpo4 polymerase, suggesting that stabilization of this bulged intermediate may be significant with regard to the biological processing of the lesion.